2016
DOI: 10.1148/rg.2016150099
|View full text |Cite
|
Sign up to set email alerts
|

MIBG in Neuroblastoma Diagnostic Imaging and Therapy

Abstract: Neuroblastoma is a common malignancy observed in infants and young children. It has a varied prognosis, ranging from spontaneous regression to aggressive metastatic tumors with fatal outcomes despite multimodality therapy. Patients are divided into risk groups on the basis of age, stage, and biologic tumor factors. Multiple clinical and imaging tests are needed for accurate patient assessment. Iodine 123 ((123)I) metaiodobenzylguanidine (MIBG) is the first-line functional imaging agent used in neuroblastoma im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 65 publications
(94 reference statements)
0
95
0
7
Order By: Relevance
“…In the 123 I-form, MIBG is ac ommercially available radiopharmaceuticalt hat is used for the SPECT imaging of humann orepinephrinet ransporter-expressing cancers. [27] In the 131 I-form, MIBG is used for targeted radionuclide therapy. [28] Adi-Boc-protected boronica cid analogue of MIBG was efficiently prepared in one step by the coupling of 3-(aminomethyl)benzeneboronic acid with di-Boc-protected 1H-pyrazole-1-carboxamidine.…”
Section: Resultsmentioning
confidence: 99%
“…In the 123 I-form, MIBG is ac ommercially available radiopharmaceuticalt hat is used for the SPECT imaging of humann orepinephrinet ransporter-expressing cancers. [27] In the 131 I-form, MIBG is used for targeted radionuclide therapy. [28] Adi-Boc-protected boronica cid analogue of MIBG was efficiently prepared in one step by the coupling of 3-(aminomethyl)benzeneboronic acid with di-Boc-protected 1H-pyrazole-1-carboxamidine.…”
Section: Resultsmentioning
confidence: 99%
“…3. Similarly, only 90 % of NB [21] and only 50 % of NB relapses [22] show MIBG uptake. Studies on NB patients reported high cumulative [23] and per-examination [24] doses of radiation exposure from PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…Eighty percent of the MIBG studies included both multiprojection static planar images and SPECT imaging, while only 13% of bone scan studies were performed with both SPECT and planar imaging. Although the addition of SPECT imaging is known to increase sensitivity, not all sites of skeletal disease (i.e., the extremities) are routinely included in standard SPECT acquisition. As such, the comparisons shown here between bone and MIBG scintigraphy were based on the planar images.…”
Section: Discussionmentioning
confidence: 99%